(untitled) (Global Journal of Science Frontier Research, 2020)
This study aimed at investigating the bacterial contamination of garri and ogi sold in markets in Keffi Metropolis, Nassarawa State Nigeria. A total of forty (40) samples, twenty (20) of garri and twenty (20) of ogi were collected from two markets (Keffi main market and Angwan lambo market) and processed using standard microbiological methods for isolation and identification of bacterial isolates. Staphylococcus aureus, Salmonella species, Escherichia coli and Klebsiella species were isolated from garri and ogi. Salmonella species was the predominant organism in garri and ogi (25% and 65%), E.coli (15% and 45%), S.aureus (5% and 30%), Klebsiella specie (0% and 10%). Antibiotics susceptibility test of Salmonella isolates against ciprofloxacin, streptomycin, chloramphenicol, ceftriaxone, ampicillin, cefurixime sodium, ceftazidine, amoxicillin/clauvulanic acid, sulphamethoxazole, and gentamicin showed that Salmonella isolates were multi drug resistant (MDR) as they were 100% resistant to six (6) of the antibiotics (ciprofloxacin, ceftriaxone, ampicillin, cefurixime sodium, ceftazidime and amoxicillin) tested and susceptible to sulphamethoxazole at 38.9%, gentamicin at 33.3%, chloramphenicol and streptomycin at 72.2%. Market Garri and Ogi were found to be contaminated with different microorganisms therefore public health standards should be adopted for the production, sales and safe handling of garri and ogi.